Impact of program characteristics on weight loss in adult behavioral weight management interventions: systematic review and component network meta-analysis - Hartmann-Boyce, J; Ordóñez-Mena, JM; Theodoulou, A; Butler, AR; Freeman, SC; Sutton, AJ; Jebb, SA; Aveyard, P (Wiley, 2022)
Objective: Behavioral weight management programs (BWMPs) for adults lead to greater weight loss at 12 months than minimal-intervention control treatments. However, there is considerable heterogeneity in the content of BWMPs and outcomes of treatment. This study assessed the contribution of individual components of BWMPs, using Bayesian component network meta-analysis. Methods: Randomized controlled trials of BWMPs in adults were identified (latest search: December 2019) and arms coded for presence or absence of 29 intervention components grouped by type, content, provider, mode of delivery, and intensity. Results: A total of 169 studies (41 judged at high risk of bias) were included in the main analysis. Six components had effect estimates indicating clinically significant benefit and credible intervals (CrIs) excluding no difference: change in diet (mean difference [MD] = −1.84 kg, 95% CrI: −2.91 to −0.80); offering partial (MD = −2.12 kg, 95% CrI: −3.39 to −0.89) or total meal replacements (MD = −2.63 kg, 95% CrI: −4.58 to −0.73); delivery by a psychologist/counselor (MD = −1.45 kg, 95% CrI: −2.81 to −0.06) or dietitian (MD = −1.31 kg, 95% CrI: −2.40 to −0.24); and home setting (MD = −1.05 kg, 95% CrI: −2.02 to −0.09). Conclusions: Future program development should consider including these components; other approaches continue to warrant evaluation of effectiveness.